2016
DOI: 10.18869/acadpub.jafm.68.225.24392
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Effects of Ramification Length and Angle on Pressure Drop and Heat Transfer in a Ramified Microchannel

Abstract: The aim of this study is to investigate the effects of ramification length and angle on pressure drop and heat transfer in a ramified microchannel. The governing equations for the fluid flow were solved by using Fluent CFD code. Computational results were compared with mathematical model values given in the literature for validation. On the basis of a water-cooled (only water and water+ethanol) smooth microchannel, ramified plates were designed into the heat sink, and then the corresponding laminar flow and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The steady-state conservation of mass, momentum and energy equations can be shown in the following compact form [5]:…”
Section: Numerical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The steady-state conservation of mass, momentum and energy equations can be shown in the following compact form [5]:…”
Section: Numerical Modelmentioning
confidence: 99%
“…Kaya [5] researched the effects of rami cation length and angle on pressure drop and heat transfer in a rami ed microchannel. Results derived from the numerical tests indicate that the pressure drop increases with increasing both the rami cation length and angle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ramiar et al (2012) numerically solved the conjugate heat transfer of a nanofluid in a 2D microchannel and investigated the effect of Reynolds number, nanoparticle conductivity. In another work, Kaya (2016) investigated the effects of ramification length and angle on pressure drop and heat transfer in a ramified microchannel. He showed that maximum temperature inside the ramified microchannel increases with increase of ramification length.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a two-dimensional study was conducted by the researches; hence the results may not be the same for actual three-dimensional problems as the additional wall effects may play a vital role in determining the exact heat transfer enhancement due to additional pressure drop. Numerous other studies have also helped in the understanding and advancement in the field of MCHS (Niazmand et al, 2010, Ramiar et al, 2012, Zade et al, 2015, Wang et al, 2015, Hamedi et al, 2016, Kaya, 2016.…”
Section: Introductionmentioning
confidence: 99%